2020
DOI: 10.1038/s41598-020-59532-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non-Celiac Gluten Sensitivity in Patients with Refractory Functional Dyspepsia: a Randomized Double-blind Placebo Controlled Trial

Abstract: Refractory functional dyspepsia (RFD) is characterized by symptoms persistence in spite of medical treatment or H. pylori eradication. No study has yet investigated the presence of gluten-dependent RFD as a clinical presentation of Non-Celiac Gluten Sensitivity (NCGS). Patients with RFD, in whom celiac disease, wheat allergy and H. pylori infection had been ruled out, followed a six weeks long gluten-free diet (GFD). Symptoms were evaluated by means of visual analogue scales; patients with ≥30% improvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 47 publications
0
33
0
3
Order By: Relevance
“…About half of our participants were gluten responsive, in line with previous studies reporting around one-third of positive responses to the DBPC gluten challenge [ 18 , 19 , 20 , 21 , 22 ]. The various prevalences of gluten challenge responsivity may be due to the high heterogeneity in the employed methodology across the studies, including dose and vehicle of gluten, duration of wash-out and gluten administration, the employed placebo, the different dietary recommendations given to participants, and the characteristics of the enrolled participants, since other studies included patients with irritable bowel syndrome (IBS) or dyspepsia [ 18 , 29 , 40 , 41 , 42 ]. The gluten and placebo we used were in line with previous published protocols [ 20 , 21 , 22 , 29 ]; the employed gluten amount was considered as being able to induce symptoms in hypersensitive patients [ 20 ]; rice starch has low fermentable capacity due to its ready absorbability and has been frequently used as a placebo [ 20 , 21 , 29 ]; the administration of a low-FODMAPs diet in the first step of the experiment to all participants likely allowed us to exclude IBS patients who usually respond to different exclusion diets [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…About half of our participants were gluten responsive, in line with previous studies reporting around one-third of positive responses to the DBPC gluten challenge [ 18 , 19 , 20 , 21 , 22 ]. The various prevalences of gluten challenge responsivity may be due to the high heterogeneity in the employed methodology across the studies, including dose and vehicle of gluten, duration of wash-out and gluten administration, the employed placebo, the different dietary recommendations given to participants, and the characteristics of the enrolled participants, since other studies included patients with irritable bowel syndrome (IBS) or dyspepsia [ 18 , 29 , 40 , 41 , 42 ]. The gluten and placebo we used were in line with previous published protocols [ 20 , 21 , 22 , 29 ]; the employed gluten amount was considered as being able to induce symptoms in hypersensitive patients [ 20 ]; rice starch has low fermentable capacity due to its ready absorbability and has been frequently used as a placebo [ 20 , 21 , 29 ]; the administration of a low-FODMAPs diet in the first step of the experiment to all participants likely allowed us to exclude IBS patients who usually respond to different exclusion diets [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…After blind gluten ingestion, symptoms recurred in 5 patients (6.4% of patients with refractory FD and 18% of gluten-free diet responders), suggesting the presence of NCGS. As shown by this study, 64 NCGS is highly prevalent among patients with refractory FD, and a diagnostic/therapeutic roadmap evaluating the effect of gluten-free diets in patients with FD should be included.…”
Section: Diet Therapy For Fdmentioning
confidence: 92%
“…Among FD cases refractory to drug therapy, gluten-dependent FD as a clinical presentation of non-celiac gluten sensitivity (NCGS) should be included. Shahbazkhani et al 64 reported a randomized, double-blind, placebo-controlled trial in which, of 77 patients with refractory FD, 50 (65%) did not respond to a gluten-free diet, while 27 (35%) showed gastrointestinal symptom improvement on a gluten-free diet. After blind gluten ingestion, symptoms recurred in 5 patients (6.4% of patients with refractory FD and 18% of gluten-free diet responders), suggesting the presence of NCGS.…”
Section: Diet Therapy For Fdmentioning
confidence: 99%
“…A randomized double-blind placebo-controlled trial in patients with refractory FD demonstrated that GFD was effective in improving gastrointestinal symptoms in 35% of patients; after blind gluten challenge, symptoms recurred in 18% of GFD responders. This last group of patients was considered confirmed NCGS [98].…”
Section: Symptoms Of Dgbi In Patients With Ncgsmentioning
confidence: 99%
“…Nutrients 2020, 11, x FOR PEER REVIEW 13 of 22 after blind gluten challenge, symptoms recurred in 18% of GFD responders. This last group of patients was considered confirmed NCGS [98].…”
Section: Symptoms Of Dgbi In Patients With Ncgsmentioning
confidence: 99%